2020
DOI: 10.3389/fimmu.2020.529035
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic Immunomodulation by PEGylated Antigenic Peptides

Abstract: Current treatments for autoimmune disorders rely on non-specific immunomodulatory and global immunosuppressive drugs, which show a variable degree of efficiency and are often accompanied by side effects. In contrast, strategies aiming at inducing antigen-specific tolerance promise an exclusive specificity of the immunomodulation. However, although successful in experimental models, peptide-based tolerogenic “inverse” vaccines have largely failed to show efficacy in clinical trials. Recent studies showed that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 67 publications
(83 reference statements)
1
19
0
Order By: Relevance
“…In the DO11.10 adoptive transfer model, we demonstrated that vaccination with PEGylated peptides led to expansion and/or de novo induction of antigen-specific Tregs. 21 To analyze the role of antigen-specific Tregs in the prevention of EAE by pMOG-PEG20 pretreatment, tolerogenic vaccination was given 2 weeks prior to EAE induction and Tregs were depleted by injection of anti-CD25 antibody 7 days prior to EAE induction. As expected, Treg depletion significantly enhanced disease already in the PBS group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the DO11.10 adoptive transfer model, we demonstrated that vaccination with PEGylated peptides led to expansion and/or de novo induction of antigen-specific Tregs. 21 To analyze the role of antigen-specific Tregs in the prevention of EAE by pMOG-PEG20 pretreatment, tolerogenic vaccination was given 2 weeks prior to EAE induction and Tregs were depleted by injection of anti-CD25 antibody 7 days prior to EAE induction. As expected, Treg depletion significantly enhanced disease already in the PBS group.…”
Section: Resultsmentioning
confidence: 99%
“… 43 45 In the OVA-model, we observed that concomitant injection of lipopolysaccharide (LPS) completely prevented the induction of Tregs upon tolerogenic vaccination with pOVA-PEG20. 21 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations